PENGARUH KUALITAS PELAYANAN, PROMOSI DAN KUALITAS INFORMASI TERHADAP KEPUTUSAN PEMBELIAN PADA PT NG TECH SUPPLIES DI KOTA BATAM - Julita, Sandra; Syaifullah, Syaifullah (LPPM Universitas Putera Batam, 2021)
The development of the trading business world shows the increasingly intense competition that exists in each company. In this study, researchers conducted research on the effect of service quality (X1), promotion (X2) and information quality (X3) on purchase decisions (Y) at PT Ng Tech Supplies in Batam City. The method that researchers use in this research is quantitative methods and data collection through the distribution of google form questionnaires. The sample obtained is 116 samples using simple random sampling. This study was assisted by data processing tools, namely SPSS version 25. The t results of this study show that service quality value is 3,212>1,981 and sig 0,002<0,05 means that service quality has a positive and significant effect on purchase decisions, promotion value is 1,364<1,981 and sig 0,175>0,05 means that promotion has a positive and insignificant effect on purchase decisions, and information quality value is 4,714>1,981 and sig 0,000>0,05 means that information quality has a positive and significant effect on purchase decisions. While the f result show the value is 45,115>2.69, that means simultaneously result is service quality, promotion and information quality have a positive and significant effect on purchase decisions.